Proteomic analysis reveals branch-specific regulation of the unfolded protein response by nonsense-mediated mRNA decay - Sieber, Jana; Hauer, Christian; Bhuvanagiri, Madhuri; Krijgsveld, Jeroen; Neu-Yilik, Gabriele; Hentze, Matthias W.; Kulozik, Andreas (Molecular & cellular proteomics, 2016)
Nonsense-mediated mRNA decay (NMD) has originally been described as a surveillance mechanism to inhibit the expression of mRNAs with truncated open reading frames (ORFs) and to contribute to the fidelity of gene expression. It is now recognized that NMD also controls the expression of physiological genes with “intact” mRNA. Stress can decrease NMD efficiency and thus increase the mRNA levels of physiological NMD targets. As stress can also inhibit translation, the net outcome for shaping the proteome is difficult to predict. We have thus analyzed de novo protein synthesis in response to NMD inhibition or the induction of mild endoplasmic reticulum (ER) stress by treatment of cells with the reducing agent dithiotreitol (DTT). For this purpose, we combined pulsed azidohomoalanine (AHA) and stable isotope labeling by amino acids in cell culture (SILAC). Labeled proteins were purified by click chemistry-based covalent coupling to agarose beads, trypsinized, fractionated, and analyzed by mass spectrometry (MS). We find that mild ER stress up-regulates the de novo synthesis of components of all three branches of the unfolded protein response (PERK, IRE1 and ATF6) without increasing eIF2α phosphorylation or impairing of protein translation. In contrast, inhibition of NMD induces de novo protein synthesis of downstream targets of the PERK and IRE1 pathways, whereas we could not detect regulation of ATF6-responsive genes. These data thus support a model that implicates a positive feedback loop of ER stress inhibiting NMD efficiency which further promotes the ER stress response in a branch-specific manner.